The effect of liquids on the stress distribution in a glass fibre reinforced plastic road tanker - Armbruster, Michael Herman (My University, 2016)
The absence of reliable design data for Glass Reinforced Plastic (GRP) road tankers has been considered an obstacle for the local design and manufacture of such vehicles. This has prompted the analysis, using Finite Element Methods (FEM) of a filament wound cylindrical shell for a monocoque road tanker. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in the fulfilment of the requirements for the Degree of Master of Science in Engineering. 1992
Keywords: Tankers--Testing; Strains and stresses; Strength of materials